Thy-1-Integrin Interactions in cis and Trans Mediate Distinctive Signaling - Hu, Ping; Leyton, Lisette; Hagood, James S.; Barker, Thomas H. (Frontiers in Cell and Developmental Biology, 2022)
Thy-1 is a cell surface glycosylphosphatidylinositol (GPI)-anchored glycoprotein that bears a broad mosaic of biological roles across various cell types. Thy-1 displays strong physiological and pathological implications in development, cancer, immunity, and tissue fibrosis. Quite uniquely, Thy-1 is capable of mediating integrin-related signaling through direct trans- and cis-interaction with integrins. Both interaction types have shown distinctive roles, even when interacting with the same type of integrin, where binding in trans or in cis often yields divergent signaling events. In this review, we will revisit recent progress and discoveries of Thy-1–integrin interactions in trans and in cis, highlight their pathophysiological consequences and explore other potential binding partners of Thy-1 within the integrin regulation/signaling paradigm.